Protection by microRNA-7a-5p Antagomir Against Intestinal Mucosal Injury Related to the JNK Pathway in TNBS-Induced Experimental Colitis - Yin, Bao; Tian-Chu, Huang; Ling-Fen, Xu (Turkish Journal of Gastroenterology, 2021)
Background: Increasing evidence shows that microRNA-7a-5p (miR-7a-5p) plays an important role in regulating the inflammatoryprocess in inflammatory bowel disease (IBD). How miR-7a-5p contributes to this process is poorly defined. The purpose of this studywas to examine whether miR-7a-5p regulates 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced inflammatory responses via the JNKpathway.Methods: Colitis was induced in male mice by intracolonic administration of TNBS; mice were divided into 3 groups: normal control (NC),TNBS, and miR-7a-5p antagomir-treated group. Inflammatory responses were estimated by disease activity index (DAI) and histologicalscores. The relative expressions of miR-7a-5p and tight junction protein, ZO-1, were detected by RT-qPCR. Western blot assays wereused to estimate the level of JNK pathway proteins and ZO-1. After miRNA-antagomir injection, the extent of colonic tissue injury andexpression levels of ZO-1 and JNK in intestinal tissue were compared.Results: miR-7a-5p and p-JNK expression were higher in the intestinal tissue of the TNBS group as compared to NC. Inhibition of theexpression of miR-7a-5p resulted in significantly decreased expression of p-JNK but increased expression of ZO-1 and promoted therecovery of intestinal mucosa.Conclusion: This work demonstrates a correlation between the JNK pathway and miR-7a-5p in TNBS-induced experimental colitis inmice, which may provide a new research direction for the treatment of IBD.